2021
DOI: 10.3390/ijms22158244
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of C-fos Activity in Neurons of the Mouse Parietal Association Cortex during Acquisition and Retrieval of Associative Fear Memory

Abstract: The parietal cortex of rodents participates in sensory and spatial processing, movement planning, and decision-making, but much less is known about its role in associative learning and memory formation. The present study aims to examine the involvement of the parietal association cortex (PtA) in associative fear memory acquisition and retrieval in mice. Using ex vivo c-Fos immunohistochemical mapping and in vivo Fos-EGFP two-photon imaging, we show that PtA neurons were specifically activated both during acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…While additional controls such as tone-alone, shock-alone, and unpaired groups are commonly employed in investigations of cued memory recall, interpretation of such control groups in the investigation of IEG expression following training is more complex, as individual neurons must respond to multiple stimuli to encode the association between them. Likely owing to this interpretational complexity, very few studies have investigated IEG expression post-training ( Radwanska et al, 2002 ; Ploski et al, 2008 ; Lonergan et al, 2010 ; Lelos and Good, 2012 ; Peter et al, 2012 ; Cho et al, 2017 ; Li et al, 2019 ; Ivashkina et al, 2021 ). Among these, Ploski et al (2008) observed increased c-fos expression between trained and control groups in LA; importantly, naïve, tone-alone, and shock-alone control groups did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…While additional controls such as tone-alone, shock-alone, and unpaired groups are commonly employed in investigations of cued memory recall, interpretation of such control groups in the investigation of IEG expression following training is more complex, as individual neurons must respond to multiple stimuli to encode the association between them. Likely owing to this interpretational complexity, very few studies have investigated IEG expression post-training ( Radwanska et al, 2002 ; Ploski et al, 2008 ; Lonergan et al, 2010 ; Lelos and Good, 2012 ; Peter et al, 2012 ; Cho et al, 2017 ; Li et al, 2019 ; Ivashkina et al, 2021 ). Among these, Ploski et al (2008) observed increased c-fos expression between trained and control groups in LA; importantly, naïve, tone-alone, and shock-alone control groups did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation to CR’s decrease in kindling epilepsy in Botterill’s paper was because of the extreme parameters used in the kindling model, resulting in increased neuronal death because of excitotoxicity ( Botterill et al., 2017 ). Mapping of c-Fos expression—a marker for neuronal activity ( Bullitt, 1990 ; Ivashkina et al., 2021 )—after GS revealed that a significant portion of CR neurons are activated in many regions of the brain, including the PIL. In addition, Ca 2+ fiber photometry ( Broussard and Petreanu, 2021 ) suggested that PIL CR neurons are significantly activated during GS but not FS in hippocampal kindling model.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, highly specific binding sites for human lactoferrin (hLf) were revealed by immunohistochemical methods in the neuronal nuclei in mouse brain [15]. The expression of the immediate early gene c-fos that is rapidly activated in response to external influences, including stress, and its product, transcription factor c-Fos, is widely used as a marker of long-term neuronal plasticity [16][17][18]. The c-Fos protein 2 of 12 is a genetic regulator for cellular mechanisms mediating the excitability and survival of neurons [19].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors regulate the expression of specific target genes in response to signaling events on the cell membrane. c-fos encodes the transcription factor that regulates the activity of effector genes and the following long-term plasticity in neurons [18,20,21]. In cell cultures, the expression of immediate early genes can be induced by diverse stimuli.…”
Section: Introductionmentioning
confidence: 99%